(untitled) (Update Dental College Journal, 2019)
The squamous odontogenic tumor (SOT) is exceptionally rare, benign, locally infiltrative neoplasm of the jaws originating from the rests of Malassez, gingival surface epithelium or from remnants of the dental lamina which is asymptomatic in nature, may present with symptoms of pain and tooth mobility. Radiographic appearance shows a triangular-shaped unilocular radiolucency associated with the roots of erupted, vital teeth. Common site of this tumor is anterior maxilla and the posterior mandible. Histologically, the formation of variable sized nests and cords of uniform, benign-appearing, squamous epithelium with occasional characterize the tumor Vacuolization and keratinization. Here we will present a case of squamous odontogenic tumor (SOT) occurring in a12 years-old female in the left side of upper jaw. Update Dent. Coll. j: 2019; 9 (2): 43-45